The Grayling Genome Reveals Selection on Gene Expression Regulation after Whole-Genome Duplication. (15th September 2018) - Varadharajan, Srinidhi; Sandve, Simen R; Gillard, Gareth B; Tørresen, Ole K; Mulugeta, Teshome D; Hvidsten, Torgeir R; Lien, Sigbjørn; Asbjørn Vøllestad, Leif; Jentoft, Sissel; Nederbragt, Alexander J; Jakobsen, Kjetill S
Abstract: Whole-genome duplication (WGD) has been a major evolutionary driver of increased genomic complexity in vertebrates. One such event occurred in the salmonid family ∼80 Ma (Ss4R) giving rise to a plethora of structural and regulatory duplicate-driven divergence, making salmonids an exemplary system to investigate the evolutionary consequences of WGD. Here, we present a draft genome assembly of European grayling ( Thymallus thymallus ) and use this in a comparative framework to study evolution of gene regulation following WGD. Among the Ss4R duplicates identified in European grayling and Atlantic salmon ( Salmo salar ), one-third reflect nonneutral tissue expression evolution, with strong purifying selection, maintained over ∼50 Myr. Of these, the majority reflect conserved tissue regulation under strong selective constraints related to brain and neural-related functions, as well as higher-order protein–protein interactions. A small subset of the duplicates have evolved tissue regulatory expression divergence in a common ancestor, which have been subsequently conserved in both lineages, suggestive of adaptive divergence following WGD. These candidates for adaptive tissue expression divergence have elevated rates of protein coding- and promoter-sequence evolution and are enriched for immune- and lipid metabolism ontology terms. Lastly, lineage-specific duplicate divergence points toward underlying differences in adaptive pressures on expression regulation in the nonanadromous grayling versus the anadromous Atlantic salmon. Our findings enhance our understanding of the role of WGD in genome evolution and highlight cases of regulatory divergence of Ss4R duplicates, possibly related to a niche shift in early salmonid evolution.